CAPITAL CONUNDRUM: INVESTIGATING THE NEXUS BETWEEN BANK CAPITALIZATION AND PROFITABILITY IN NIGERIA - Ogunjimi, Adeola (Economics and Statistics Research Journal (ESRJ), 2023)
The profitability of commercial banks is of paramount importance to the overall health and vitality of an economy. This study delves into the determinants of bank profitability in Nigeria, particularly after a significant round of bank recapitalization in 2005. We address key questions regarding the factors influencing bank profitability in the post-recapitalization era and assess the impact of market power on bank returns. Through empirical analysis, we identify the driving forces behind profitability in Nigeria's commercial banks and examine the relative significance of market power among these determinants. Our findings offer valuable insights for policymakers and stakeholders in fostering a robust financial sector that can effectively support economic growth.